Knowledge, attitude, and practices of parents with children of first time and recurrent febrile seizures - Willy Gunawan; Komang Kari; Soetjiningsih Soetjiningsih (Paediatrica Indonesiana, 2008)
Background Febrile seizure is a condition of emotionally trauma-tize for most parents. It is believed that parents whose childrenexperienced febrile seizures before, have a better knowledge, at-titude, and practices (KAP) in responding to the seizure. Hencethe fear and emotional disruption that febrile seizures can causein the family, prevention should be addresses.Objective To find if there was any differences in KAP of parents ofchildren with recurrent febrile seizures compares to parents withchildren of first time febrile seizures.Methods A cross sectional study was conducted on parents whohave children aged between 6 months to 5 years old with eithersimple febrile seizures, complex febrile seizures or recurrent febrileseizures admitted to Pediatric Neurology Clinic ofSanglah Hospi-tal. Subjects were selected consecutively and were grouped intogroup of parents with children of first time seizures and parentswith children of recurrent febrile seizures group.Results Based from summated rated method, it seemed thatparents of children with recurrent febrile seizures have higherKAP of febrile seizures and was statistically different (A=O.OOO;P < 0.001). Analysis of covariance (ancova) showed that education(P=0.013) had an influence in the KAP of the parents. Otherancova revealed that children's age and sex have significantinfluence.Conclusion The KAP of parents with children of recurrent febrileseizures are higher and have statistically different compared withparents of children with first time febrile seizures.